(untitled) (Innovaciones Educativas, 2022)
This article is the result of qualitative research with a narrative approach in which we initially sought to inquire about the contribution of students enrolled in the subject Writing Process I of the English Teacher Training Program at Universidad Nacional de Mar del Plata. For this purpose, we conducted questionnaires to the entire group of students who had taken the course in 2019. Then, we proceeded to search for first-person accounts through narratives of experiences. In this way, we sought to understand how the students perceive the contributions of the subject mentioned above. On the other hand, during text analysis, the dimension of knowing how to be a teacher emerges, closely related to the affections and the experience significance for teacher training. The contributions of the group of participants presented significant findings that showed that future teachers care about their students, create interpersonal bonds that strengthen learning, and in their continuous learning process, they understand that there is another who needs to be accompanied. These findings clearly show that teacher training needs personal mediation and must be sustained by experience.